La relación: matemática-semiosis-argumentación, en la elaboración de diseños didácticos - León C., Olga Lucía (Revista Científica, 2006)
This article presents results of research on the relations among the mathematical, communicative, cognitive, and curriculum components, required for the didactic designs looking forward the formulation of geometric relations such as the Pythagoream relation. The general investigative design was structured since the didactic engineering. The analysis are presented here a priori and a posteriori of one of the workshops of the structured didactic designs. The two levels of analysis engage the didactic development in the pedagogical dimension, and the semiotic-argumentative development in the mathematical dimension. Thus the results provide and interpretive framework of the interaction between didactic processes and development of mathematical knowledge in a school context.